2022
DOI: 10.1002/mp.15473
|View full text |Cite
|
Sign up to set email alerts
|

Design, realization, and characterization of a novel diamond detector prototype for FLASH radiotherapy dosimetry

Abstract: Purpose FLASH radiotherapy (RT) is an emerging technique in which beams with ultra‐high dose rates (UH‐DR) and dose per pulse (UH‐DPP) are used. Commercially available active real‐time dosimeters have been shown to be unsuitable in such conditions, due to severe response nonlinearities. In the present study, a novel diamond‐based Schottky diode detector was specifically designed and realized to match the stringent requirements of FLASH‐RT. Methods A systematic investigation of the main features affecting the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 57 publications
(122 reference statements)
2
30
0
Order By: Relevance
“…The linearity tests, whose results are reported in Figure 1, demonstrate that the fD response is linear at least up to the maximum DPP of 11.9 Gy available in this study, well in the UH‐DPP range. This confirms the results previously reported for fDs by the authors 33 . Two experimental data shown in Figure 1a and obtained by using the 30 and 35 mm applicators, that is, the ones at the highest DPPs in the plot, deserve a specific comment.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The linearity tests, whose results are reported in Figure 1, demonstrate that the fD response is linear at least up to the maximum DPP of 11.9 Gy available in this study, well in the UH‐DPP range. This confirms the results previously reported for fDs by the authors 33 . Two experimental data shown in Figure 1a and obtained by using the 30 and 35 mm applicators, that is, the ones at the highest DPPs in the plot, deserve a specific comment.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, an fD prototype was investigated, whose physical properties were recently reported by Marinelli et al 33 . It consists of a diamond Schottky diode, based on the same working principle of the commercially available PTW microDiamond (mD) (PTW‐Freiburg, Germany) 35,36 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Maximum dose rate achievable with applicator 10 cm is beyond 1000 Gy/s, with a dose per pulse above tition rate. A PMMA phantom was built for the insertion of the UTIC and a specially modified diamond detector (flash-diamond) for UHDR 22 which was used as a reference dosimeter (Figure 3). Flash-diamond was placed at 30 mm transversal distance from UTIC axis at the same depth of material.…”
Section: Experimental Measurementsmentioning
confidence: 99%